2019
DOI: 10.1080/13603124.2019.1580773
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of department heads’ job autonomy, role clarity, and self-efficacy for instructional leadership

Abstract: Department heads are increasingly responsible for instructional leadership. Therefore, it is important to understand the antecedents of self-efficacy in their work, which can motivate them to increase their leadership efforts. Our theoretical model depends on principals' feedback for department heads, department heads' trust in their principals, and perceptions of time pressure. We argue that the relational trust between department heads and principals creates social exchanges that catalyze department heads' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…These tasks were not fulfilled by the senior leaders at Andes and, as explained by the principal, his "hands-off" approach sought to demonstrate his trust in teachers' capacities. Trust, of course, is a key resource for instructional leadership that circulates along the leadership hierarchy and among actors at the same level (Brandmo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tasks were not fulfilled by the senior leaders at Andes and, as explained by the principal, his "hands-off" approach sought to demonstrate his trust in teachers' capacities. Trust, of course, is a key resource for instructional leadership that circulates along the leadership hierarchy and among actors at the same level (Brandmo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In secondary schools, studies have documented that principals’ leadership functions are exercised directly and indirectly through the distribution of some of these functions to department heads (Brandmo et al, 2021; Harris et al, 1995; Plessis and Eberlein, 2018). Principals must ensure that strong organization, policies and routines are in place to effectively distribute leadership functions to department heads (Bendikson et al, 2012; Mascall et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, findings from two recent studies on Norwegian school principals established a direct link between the capacity for instructional leadership and principals’ self-efficacy (Skaalvik, 2020). Further, a study on Norwegian heads of departments revealed a similar pattern; a capacity for instructional leadership was positively related to job satisfaction and negatively related to turnover intention (Brandmo et al, 2019). Our study follows this line of reasoning and formulates the following research question:…”
Section: Introductionmentioning
confidence: 89%
“…Zira yeterlilik hissi sayesinde, bu bireyler, liderliğin yükleyebileceği maliyetleri nasıl dengeleyebileceklerini tahmin edebilmektedirler. Herhangi bir ek fayda sağlamasalar da liderlik rolünü benimsemeleri ve bu rol sayesinde görev ve sorumluluk duygusunu tatmin edebilmeleri onlar için yeterli olmaktadır (Brandmo, Tiplic ve Elstad, 2021). Bu çıkarımların ışığında aşağıdaki hipotez geliştirilmiştir: H4: Liderlik özyeterliği liderlik etme motivasyonunu olumlu yönde yordamaktadır.…”
Section: Liderlik Etme Motivasyonunun Aracılık Etkisiunclassified